PEDAGOGICAL FEATURES OF DEVELOPING FUTURE TEACHERS’ PROFESSIONAL COMPETENCE THROUGH THE USE OF ARTIFICIAL INTELLIGENCE (International journal of artificial intelligence, 2025)
The rapid advancement of artificial intelligence (AI) technologies has introduced new opportunities for enhancing the professional competence of future teachers. In the modern educational paradigm, the integration of AI into pedagogical practice is not merely an auxiliary tool but a transformative factor that reshapes teaching methodologies, learning strategies, and assessment mechanisms. This article examines the pedagogical features of developing professional competence among prospective educators through the application of AI-based technologies. Special attention is devoted to the ways in which AI contributes to strengthening cognitive, methodological, and reflective skills, while simultaneously fostering adaptability to the rapidly changing demands of the digital age.